District 9 [videorecording (DVD)] - Copley, Sharlto, 1973-; Cope, Jason; James, David, 1972-; Haywood, Vanessa; Gaduka, Mandla; Nkosi, Kenneth; Khumbanyiwa, Eugene; Minnaar, Louis; Young, William Allen, 1953-
Back in the 1980s, a giant spacecraft stalled in the skies over Johannesburg. 1.8 million of the aliens that were aboard were rescued, and placed in a refugee camp--District 9. Over the next 20 years, District 9 became a teeming shantytown like so many others in the developing world. Although there is evidence that the extraterrestrials represent an advanced civilization, their lives on Earth are marked by squalor, dysfunction, and xenophobic hostility. Now, the mass eviction of the aliens is due to commence, overseen by the military/corporate entity MultiNational United. Middle manager Wikus Van De Merwe finds himself in charge, and cannot believe the good luck of his sudden promotion, until events spin out of control, and he realizes he is little more than a pawn in a horrific multinational/intergalactic experiment.